Differences in pragmatic skills between bilingual Turkish immigrant children in the Netherlands and monolingual peers. (August 2019) - Backus, Ad; Yağmur, Kutlay
In bilingualism studies, comparing the competence of mono- and bilingual speakers is common, but it comes with certain limitations. In immigration contexts, many studies concentrate on the skills of immigrant pupils in the mainstream language. In order to account for educational underachievement of minority children, gaps in their language development are often documented by comparing mainstream pupils with immigrant children. Competence in the first language (L1), on the other hand, receives very little attention, despite the fact that it is often assumed that L1 competence has an impact on second language acquisition. Here, we present the findings of an empirical study that compared bilingual Turkish immigrant children ( n = 30) in the Netherlands with monolingual Turkish peers ( n = 30) in Turkey. Contrary to most other such studies, we focus on the development of socio-pragmatic skills. The evidence shows that, from the viewpoint of monolingual conventions, the immigrant children lag behind in their command of these skills. Also after controlling for socioeconomic status, bilingual Turkish immigrant children display much lower knowledge of the socio-pragmatic skills than monolingual Turkish children. The causes of this difference can be attributed to the limited Turkish input in the immigration context.